Standardized IMGT® Nomenclature of Salmonidae IGH Genes, the Paradigm of Atlantic Salmon and Rainbow Trout: From Genomics to Repertoires - Magadan, Susana; Krasnov, Aleksei; Hadi-Saljoqi, Saida; Afanasyev, Sergey; Mondot, Stanislas; Lallias, Delphine; Castro, Rosario; Salinas, Irene; Sunyer, Oriol; Hansen, John; Koop, Ben F.; Lefranc, Marie-Paule; et al. (Frontiers in Immunology, 2019)
In teleost fish as in mammals, humoral adaptive immunity is based on B lymphocytes expressing highly diverse immunoglobulins (IG). During B cell differentiation, IG loci are subjected to genomic rearrangements of V, D, and J genes, producing a unique antigen receptor expressed on the surface of each lymphocyte. During the course of an immune response to infections or immunizations, B cell clones specific of epitopes from the immunogen are expanded and activated, leading to production of specific antibodies. Among teleost fish, salmonids comprise key species for aquaculture. Rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar) are especially important from a commercial point of view and, have emerged as critical models for fish immunology. The growing interest to capture accurate and comprehensive antibody responses against common pathogens and vaccines has resulted in recent efforts to sequence the IG repertoire in these species. In this context, a unified and standardized nomenclature of salmonid IG heavy chain (IGH) genes is urgently required, to improve accuracy of annotation of adaptive immune receptor repertoire dataset generated by high-throughput sequencing (AIRRseq) and facilitate comparisons between studies and species. Interestingly, the assembly of salmonids IGH genomic sequences is challenging due to the presence of two large size duplicated IGH loci and high numbers of IG genes and pseudogenes. We used data available for Atlantic salmon to establish an IMGT standardized nomenclature of IGH genes in this species, then applied the IMGT rules to the rainbow trout IGH loci to set-up a nomenclature, which takes into account the specificities of Salmonid loci. This unique, consistent nomenclature for Salmonid IGH genes was then used to construct IMGT sequence reference directories allowing accurate annotation of AIRRseq data. The complex issues raised by the genetic diversity of salmon and trout strains are discussed in the context of IG repertoire annotation.